13.7% Efficiency Small-Molecule Solar Cells Enabled by a Combination of Material and Morphology Optimization - Yue, Qihui (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.